Effectiveness of human resource management practices on the retention of mathematics teachers: A case of public secondary schools in Arusha city council - Mleli,Aggrey Adelbert (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Human Resource Management (MSc-HRM) of Mzumbe University.